Thinking Ableism through Heterocissexism. A Critical Review of Fraser’s Redistribution-Recognition Pair from a Queer-Crip Perspective - Leani, Lautaro (Scenari, 2023)
The philosophical framework of justice proposed by Nancy Fraser during the 1990s establishes two equally crucial dimensions of justice: redistribution, linked to the allocation of economic goods, and recognition, linked to the assignment of social status. This division makes it possible to distinguish between transformative strategies that intervene in the causes of social injustices and affirmative strategies that focus on their effects. However, the author’s treatment of her notion of “two-dimensional category”, which combines inequalities of redistribution and recognition, has limits for thinking about the functioning of certain systems of social subordination and the situation of certain social groups. In this paper, I will use a queer-crip perspective to argue that both heterocissexism and ableism are two-dimensional categories, since they structure an unequal status system, but also sustain, define, and naturalize the capitalist mode of production and are functional to its distribution of economic goods. This critical review allows us to adapt the Fraserian framework to the current socio-political context.